Neurological disorders and small bowel dysmotility. Issue 3 (May 2022) - Kamperidis, Nikolaos; Nightingale, Jeremy
Abstract : Purpose of review: Small bowel dysmotility is common in the context of neurological disorders. Overlooking it can have an adverse impact on patient's quality of life and neurological outcomes. This review focuses on describing the mechanisms and effects of enteric dysmotility in neurological patients and providing treatment options. Recent findings: Small bowel dysmotility is prevalent among neurological patients. The definition and diagnosis of small bowel dysmotility is a challenge; however, up to two-thirds of neurological patients may experience associated symptoms. Small bowel dysmotility can affect the absorption of nutrients and medication, impacts on social and professional function and can result in malnutrition and its associated morbidity and mortality. Summary: Small bowel dysmotility due to a neuropathy can result from acute or chronic disorders in the central and peripheral nervous system and includes the cerebral cortex, brain stem, spinal cord, parasympathetic (vagus) and sympathetic nerves and the myenteric and submucosal plexuses of the intestine. Generalized muscle disorders can also cause an enteral myopathy. Generally, the disorders may be degenerative or inflammatory. Both enteric neuropathy and myopathy may cause symptoms of abdominal pain, nausea/vomiting, bloating, constipation or diarrhoea and can cause malnutrition. The symptoms need to be addressed in order of importance to the patient and malnutrition prevented or treated.